Measuring terrorism - Young, Joseph (Terrorism and political violence, 2019)
In the conceptual literature on terrorism, there is no shortage of answers to the question: “What is terrorism?” Indeed, the terrorism literature has been heavily criticized for a deluge of definitions. And yet the booming quantitative terrorism literature generally examines a narrow set of “what is terrorism?”: how country-level factors explain variation in the number of terrorist attacks. This article demonstrates the variety of ways in which scholars currently operationalize terrorism and compares them to the ways it could be operationalized. I replicate studies using alternative operationalizations of terrorism to examine the consequences of the terrorism literature’s collective bet to focus on attack counts at the country level. Finally, I discuss the implications of the narrow set of operational choices with an eye towards how a greater variety of approaches would produce a more robust research agenda.